Total Synthesis of Proposed Structure of Yuremamine and All Diastereomers Using [3+2]‐Cycloaddition of Platinum‐Containing Azomethine Ylide. Issue 9 (14th July 2015) - Ohyama, Tomoya; Uchida, Masako; Kusama, Hiroyuki; Iwasawa, Nobuharu
Abstract Total synthesis of the proposed structure of yuremamine has been achieved for the first time based on the intermolecular [3+2]‐cycloaddition reaction of the platinum‐containing azomethine ylide. All the possible diastereomers of yuremamine were also synthesized via the common intermediate. Through these syntheses, it was confirmed that the proposed structure of yuremamine and the diastereomers differ from the natural product.